(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to history of the gathering and holding the second and the last Congress of UAOC 1921 - specimen, at the head of Vasil Lypkivsky. The main attention is payed to the problem of learning and publishing sources, relations between the Church and the State in 1920-1930th and strengthening of pressure, putting to UAOC from GPU (The State Political Department).